CONFIRMATORY COMPOSITE ANALYSIS OF BUSINESS ADMINISTRATION GRADUTES' NEEDS TO UPSKILL - lawatin, Chawala (Pathumthani University Academic Journal, 2022)
The study's aims are as follows: 1) investigate the need for graduate business administration for upskilling. 2) Using confirmatory composite analysis, investigate the fundamental literacies, competencies, and character qualities that influence graduate business administration upskilling. The sample is a business administration graduate from the management science faculty of Valaya Alongkorn Rajabhat University in Patumtani, which is under Royal Patronage. According to the Soper technique, the sample size is 150. The findings indicate that recent business administration graduates need to improve their skills. The model had relevant to empirical data. All indicators in the measuring model were of high quality and appropriate. The structural model had three paths that are significantly different, indicating that all three assumptions were accepted. Assuming that people need to improve their skills in all three areas, the character of quality had the highest association to upskilling.